Characterisation of protein nanotubes by ToF‐SIMS imaging. (22nd June 2012) - Poleunis, Claude; Dupont‐Gillain, Christine; Demoustier‐Champagne, Sophie; Delcorte, Arnaud; Kalaskar, Deepak
Abstract : A growing number of nano‐objects such as nanotubes, capsules or beads are being developed for various biological and medical applications. In particular, the use of polymer templates for the synthesis of nanomaterials, using layer‐by‐layer assembly, has become a method of choice due to its simplicity and versatility in shapes and dimensions. However, chemical characterisation of these nano‐objects still remains challenging. Here, we report the use of ToF‐SIMS, especially in the imaging mode, for the characterisation of collagen‐based nano‐ and microtubes deposited on surfaces, with a view to applications in biomaterials science. The classical univariate or multivariate Principal Component Analysis (PCA) spectral data treatments do not display any significant differences between the nanotubes with different layer sequences (protein‐polymer or polymer‐protein). However, the layer sequences are clearly differentiated by the ToF‐SIMS images acquired at high lateral resolution (0.3 µm), combined with high mass resolution (m/Δm > 5000 @ 29 m/z), because of the complexity of the protein spectral pattern. These results highlight the importance of imaging for chemical analysis of nanoparticles‐coated samples. This study has particular relevance for nanoscale imaging of biointerfaces. Copyright © 2012 John Wiley & Sons, Ltd.